Avoiding delays in diagnosis: the importance of proactive liaison and education of staff in the general hospital. Issue 6 (28th October 2014) - Walder, Anna; Green, Robert; Soni, Sujata
Abstract : Purpose: – The purpose of this paper is to illustrate the difficulties patients with intellectual disabilities face when they present to a general hospital with ambiguous symptoms and highlights the importance of adequate training for general staff in caring for people with learning disabilities. Design/methodology/approach: – The authors describe the pathway of a person with a learning disability and mental health problems from A&E, through a general hospital, to discharge and the problems encountered in terms of diagnostic clarity and subsequent treatment. Findings: – Delay in recognising a psychiatric cause for his symptoms and wrongly attributing his symptoms to his learning disability may have led to a protracted admission and invasive tests. Originality/value: – Education of healthcare professionals and proactive liaison work can help improve outcomes for people with intellectual disabilities when they are admitted to generic services.